2013
DOI: 10.7448/ias.16.1.17354
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the implementation of PEPFAR's anti‐prostitution pledge and its implications for successful HIV prevention among organizations working with sex workers

Abstract: IntroductionSince 2003, US government funding to address the HIV and AIDS pandemic has been subject to an anti-prostitution clause. Simultaneously, the efficacy of some HIV prevention efforts for sex work in areas receiving US government funding has diminished. This article seeks to explain why.MethodsThis analysis utilizes a case story approach to build a narrative of defining features of organizations in receipt of funding from the President's Emergency Plan for AIDS Relief (PEPFAR) and other US funding sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…However, criminalization, stigma, and a lack of funding to support sex worker-led programs continue to impede collectivization among sex workers [1,24]. Akin to the US PEPFAR anti-prostitution pledge, the PCEPA reduces access to community-led services and jeopardizes funding for and development of critical sex workerled supports, in addition to further conflating sex work with trafficking [6,10,27,28]. Legislative reform to sex work laws in New Zealand and parts of Australia exemplify the benefits of decriminalizing all aspects of sex work for enabling safer occupational conditions for sex workers, with demonstrated impacts on increased access to health services and improved workplace safety [29][30][31].…”
Section: Characteristicmentioning
confidence: 99%
“…However, criminalization, stigma, and a lack of funding to support sex worker-led programs continue to impede collectivization among sex workers [1,24]. Akin to the US PEPFAR anti-prostitution pledge, the PCEPA reduces access to community-led services and jeopardizes funding for and development of critical sex workerled supports, in addition to further conflating sex work with trafficking [6,10,27,28]. Legislative reform to sex work laws in New Zealand and parts of Australia exemplify the benefits of decriminalizing all aspects of sex work for enabling safer occupational conditions for sex workers, with demonstrated impacts on increased access to health services and improved workplace safety [29][30][31].…”
Section: Characteristicmentioning
confidence: 99%
“…Allman et al (2010) reported significant confusion among HIV prevention implementation partners supported by the United States as a result of the 2005 Anti-Prostitution Pledge policy of the US PEPFAR program. 22 Many organizations were reportedly unclear whether and how they might provide services to SW, and some reported avoiding the provision of such services to SW so as to comply with the pledge, despite the fact that PEPFAR permit SW services. 23 In India, negative attitudes and practices of government health care workers toward SW have been shown to be a significant barrier to accessing antiretroviral drugs (ARV).…”
Section: Marp and Public Policiesmentioning
confidence: 99%
“…12 The advent of the 2003 “Prostitution Pledge” policy requirement for U.S. Federal (PEPFAR) funding reduced programmatic engagement with SW in some settings. 3,13,14 This has been associated with reduced financing of HIV programs for SW, particularly programs which funded SW-led organizations. 15 Finally, the very high HIV incidence among women in Southern Sub-Saharan Africa in 2001–2005, meant that HIV studies which required HIV sero-conversion endpoints (microbicides, HIV vaccines, PrEP)) could be conducted among the general population of reproductive aged women, markedly reducing the necessity of recruiting SW.…”
Section: Introductionmentioning
confidence: 99%